VISUALIZING THE BODY - MITCHELL, DAVID; Snyder, Sharon (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This seminar will examine key structural and representational concerns related to disability in popular and documentary film. While the course will cover some important aspects of film history, it is primarily intended to develop analytical acumen with respect to the function of disability as a meaning-making device in visual media. In doing so, we will seek to expose the prevalence of disability as an aspect of characterization, metaphor, and plot generation. Our efforts will also seek to identify critical (i.e. repeated and naturalized) narrative formulas bequeathed to the social construction of disability. The key objectives of the seminar will entail efforts to understand the means by which disability has come to be recognized as a series of biologically determined properties interpreted as primarily detrimental to human organisms and communities. Film both participates in and interrogates such associations and thus embodies one of the primary textual mediums in contemporary (primarily Western) societies. To study film is to isolate the various social contexts and ideologies that make disability apparent as a process of embodiment grafted upon those marked as deviant.